Layanan Pendidikan Berkualitas Bagi Siswa Berkebutuhan Khusus Melalui Aplikasi Informasi Terpadu SLBN 25 Sintang (INTERTANG) - Nur Rohmah (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
Inclusive education in Indonesia faces challenges in ensuring accessibility, efficient education management and effective communication, especially for students with special needs. SLBN 25 Sintang developed the Integrated Information Application (INTERTANG) as a technology-based solution to overcome these challenges, but its implementation has not been fully optimised. This research identifies knowledge gaps related to the effectiveness of the INTERTANG application in supporting inclusive education services through information access, data management and communication. The methodology used is a literature review with a qualitative descriptive approach, which examines literature sources related to inclusive education, information technology and education management. The results showed that INTERTANG significantly improved information access through a transparent and easily accessible data-driven platform, improved education management through efficient data management features and enhanced communication between students, parents and teachers. In addition, the app contributes to improving the quality of education services and becomes a strategic tool in supporting an inclusive curriculum. The implication of this research is that INTERTANG can be a model to be implemented in other schools and strengthen technology-based inclusive education management. This research recommends further development in educator training and expansion of the app's implementation in a broader context to improve the quality of inclusive education in Indonesia. This research contributes to the development of a technology-based inclusive education model that can be applied in Indonesian schools, as well as providing directions for improving the effectiveness of technology app implementation in the context of special needs education